(3fXQjI GdeQGLYI (B/s - (3eMeO, fUQ UGdMs ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2015)
(3jVe bQGAI adSajI aj fXQjI GdeQGLYI hbQGAI JMdjdjI GfJbGOjI ddOQGSGJ GdSGHbI aj eLGd fXQjI GdeQGLYI, GdEWGQ GdfXQj GdebJQM ddeQGLYI(B.s
(3HHdjhZQGajG(B: (3U(B.297-312s
Keywords: (3GdQbGHIs; (3eQGLYI GdMSGHGJs